Designing an adaptive-predictive system to control hydrodynamic modes of oil transportation - Kuchmystenko, Oleksandr; Shavranskyi, Mykhailo; Puk, Yurii (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the process of automated control over the operation of pumping stations along the main oil pipeline during start-up, stop, and pressure maintenance while oil pumping. Disturbances are considered as deterministic parametric variations of the coefficient of hydraulic resistance, which depend on changes in pressures, flows, including oil viscosity. A control system has been designed that solves the problem of integrating recursive identification of model parameters with predictive formation of control effects in a single loop that covers start-up, operating mode, and compensation for disturbances. The main idea of automation is to transfer the functions of controlling the oil pipeline from pumping station operators to the dispatch center. An adaptive-predictive control structure has been proposed that combines recursive identification of parameters, state assessment, and optimization predictive formation of control effects. The system integrates a Kalman filter for real-time state assessment and a module for recursive updating of model parameters. This provides online adaptation of the mathematical model of the facility without personnel intervention. The application of the proposed approach reduces the accumulation of the integrated error in flow control under the operating mode by approximately 87 percent. After a viscosity jump, the flow does not go beyond the technological tolerance of ± 2 percent. The improvement in control quality is explained by the system’s capability to predict the dynamics of the facility and compensate for uncertainties before their impact on the controlled variables. The algorithm automatically processes the full cycle: controlled start-up, entry into the operating mode, and maintaining pressures within the specified limits. The results could be implemented in SCADA systems for oil pumping stations to be controlled from the dispatch center. This would increase the economic efficiency and stability of oil transportation modes